Available methane from anthracite by combining coal seam microflora and H2O2 pretreatment. (6th September 2020) - Guo, Hongguang; Han, Qing; Zhang, Jinlong; Liang, Weiguo; Huang, Zaixing; Urynowicz, Michael; Ali, Muhammad Ishtiaq
Summary: The conversion of coal to methane by anaerobic microorganisms is an efficient, clean, and green way to utilize coal. However, methane production is relatively low due to the low bioavailability of coal. H2 O2 has been demonstrated to increase methane production by transferring coal to liquid organics. Little is known about the bioavailability of residual coal after H2 O2 pretreatment. Here, H2 O2 was employed to pretreat anthracite, and the potential of residual coal to produce methane was analyzed. The optimum conditions for pretreatment were 30% H2 O2 for 12 hours when the methane production reached 254.97 μmol/g coal, increased by 24.98% compared with that in unpretreated coal. The results of FTIR showed that the substitutions of aromatics, alkanes rings, aliphatics, and even C=C structure in coal were depolymerized and oxygen‐containing functional groups were generated after pretreatment with H2 O2 . The oxygen‐containing functional groups were further degraded by anaerobic microflora. The XRD results showed that the crystal structure of coal decreased after pretreatment with H2 O2 following 27 days of cultivation. These results suggested that H2 O2 pretreatment mainly altered coal by increasing the oxygen‐containing functional groups and decreasing the crystal structure of coal to facilitate coal biodegradation and enhance biomethane production. The effect of H2 O2 on the production of biomethane was not only to produce easily degradable organics, but also to change the coal structure and promote the degradation of residual coal. Therefore, the enhancement of biomethane production by H2 O2 pretreatment on surface bioconversion and underground coalbed methane mining should take the increase methane yield from residual coal into account. Abstract : H2 O2 pretreatment can enhance methane production by increasing bioavailability of residual coal besides of producing easily degradable organics which should be taken into account when it was carried out in surface bioconversion and underground coalbed methane mining. The residual anthracite after treated with H2 O2 was more suitable for biodegradation whose optimum conditions were 30% H2 O2 for 12 hours with the maximum methane production of 254.97 μmol/g coal. The crystal structure was decreased, the C=C structure were depolymerized, and the oxygen‐containing groups were increased after H2 O2 treatment, while the oxygen‐containing functional groups and crystal structure of coal were decreased after anaerobic degradation for 27 days.